Iklim Sekolah Inklusi (Penelitian di SMK X Jakarta) - Weny Savitry S. Pandia; Penny Handayani; Novita W. Sutantoputri (Universitas Katolik Indonesia Atma Jaya, 2015)
Inclusive schools in Indonesia have increased rapidly. They are supported by the government policy to organize inclusive education related to equal rights to education for all children. In Middle-Vocational School (Sekolah Menengah Kejuruan (SMK)), which is the final level of secondary education, students need to have a good preparation before continuing their education to a higher level or plunge into the world of work. The readiness can be achieved if students have good learning achievement. One of the factors that influence learning achievement is a positive school climate. This study aimed to identify the school climate‟s perception of students with special needs and regular, teachers, principals, and parents in SMK X, Jakarta. Results indicated that students, teachers, and parents at SMK X have positive perception of the school climate. As for the students, the perception is quite positive except in the case of bullying. Teachers have positive perceptions of school climate in varied levels.